Spiritual cleansing: A case study on how spirituality can be mis/used by a company - Claudia Groß (Management Revue, 2010)
Organisational spirituality has gained popularity. While some authors see a spiritually fulfilling workplace as a benefit for employees and organisations alike, critical authors point out the potentially totalising effects of organisations that try to colonise employees' minds, hearts and souls. Whereas most existing critical studies are based on literature analyses and mainly refer to societal developments and how organisations are affected by them, the paper at hand provides a single case study on the organisational level. The case study allows a more detailed examination of how organisations can employ spirituality to serve organisational goals. The article identifies three aspects in which workplace spirituality can be misused: to mislead members about the nature of their work, about what an organisation can offer to its members and about the societal value of an organisation.
Keywords: 650; Spirituality; critical management studies; normative control; direct selling; multi-level-marketing